SCHOOL EFFECTIVENESS INDICATORS OF THE DUTCH INSPECTORATE AND ITS COMPARISON TO INDICATORS USED IN INDONESIA IN PRIMARY EDUCATION - Susanah Susanah (FKIP ULM, 2012)
This article explores the school inspection framework and indicators of educational effectiveness used in the Netherlands and Indonesia. The Dutch inspectorate carries out school inspection in the form of periodical quality inspection in which schools are assessed through desk-research analysis. Meanwhile, Indonesia employs school accreditation boards and school inspectors to evaluate school quality through desk-analysis and visitation. Both countries apply rather similar indicators of educational effectiveness. The Netherlands uses in-depth content analysis, however, Indonesia uses a rather broad one.